Analisis Yuridis Terhadap Larangan Kegiatan Pada Bulan Ramadhan Dalam Perspektif Konstitusi - Al Hasanie, Ryan; Saputra, Dadin Eka; Ridho, M. Rosyid (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Ramadan is a month that is holy and full of mercy, a month full of favors and full of forgiveness for every Muslim. To create a solemn and comfortable Ramadan fasting for Muslims in the City of Banjarmasin, the government of the City of Banjarmasin passed the RegionalxRegulation of the City of Banjarmasin Number 4 of 2005 concerningxAmendments to the RegionalxRegulationxof the City of Banjarmasin Number 13 of 2003 concerning Prohibitionxof Activitiesxduring the Monthxof Ramadan. This regional regulation contains a ban on opening stalls, restaurants, rombong, cafes and the like during fasting time or during the day and is only allowed to sell in the afternoon at 17.00 WITA. As well as a ban on activities in entertainment venues for a full month. This regional regulation also includes sanctions that apply to business actors and the public who are found to have violated this regional regulation. The formulation of thexproblem inxthis studyxis how to regulate the law regarding the prohibition of activities in the month of Ramadan according to the Regional Regulationxof the City of Banjarmasin Number 4 of 2005 concerning Amendments to the RegionalxRegulation of the City of Banjarmasin Number 13 of 2003 concerning the Prohibitionxof Activities in the Monthxof Ramadan and how is the Juridical Analysis of the RegionalxRegulations of the City of Banjarmasin Number 4 of 2005 concerning Amendments to Banjarmasin City Regional Regulation Number 13 of 2003 concerning Prohibition of Activities in the Month of Ramadan in a Constitutional Perspective. Thextype of research used is casexstudy research using normative methods. In thisxstudy, researchers seek and obtain information through literature, journals, laws and regulations, internet browsing, and other documents. In this case the researcher looks for the books needed.